Social Networking Trend in Improving Educational Leadership Competency in Higher Learning: Systematic Data Analysis - Antoni Ludfi Arifin (STAI Hubbulwathan Duri, 2021)
This study examined social network trends in improving educational leadership quality and higher learning outcomes through systematic data analysis. Forward or backwards, the quality of human resources and scholarly output in the academic environment is closely related to social networking, which is increasingly becoming a phenomenon today. The researcher has carried out a series of data collection through electronic searches in several international publications in various scientific communication contexts to understand this. Furthermore, the analysis process includes understanding the study questions, coding, analysis, and in-depth interpretation to obtain valid and reliable study findings that answer this study's questions. Our e-search, especially on the Google Scholar data source, ERIC publications, and other online data sources from the 2010 to 2021 publications, was prioritized. Based on the discussion of results and observations of current social networking trends, it can be concluded that social networking brings benefits such as building social relationships, communication, keeping up with renewal, more personal relationships, more genuine connections, advertising, and other networking among educational leaders worldwide.